ANALYSIS OF COMPETITIVENESS OF INDONESIAN PLAITINGS PRODUCTS IN THE INTERNATIONAL MARKET (RCA, EPD, DAN X MODEL POTENTIAL EXPORT PRODUCT ANALYSIS) - Muh Nurkhamid (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The article entitled Analysis of Competitiveness of Indonesian Plaitings Products in the International Market is written with a descriptive statistical approach and with the Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD) and X-Model Potential Export Product analysis methods. The three methods are used to determine the competitiveness of Indonesian plaitings products compared to major plaitings product exporting countries as well as competitiveness in some of Indonesia's main export destination countries. Data was downloaded from UN Comtrade in the form of the export value of plaitings products in several countries as well as the export value of Indonesian plaitings products in several major export destination countries from 2017 to 2022. The results of data processing show that Indonesia's average RCA value is 3.55, the EPD category is 'rising star', and Indonesia's export potential is 'optimistic'. With these three indicators, Indonesian plaitings products have high competitiveness among competing countries exporting plaitings products in the international market. Furthermore, the competitiveness position of Indonesian plaitings products in export destination countries varies. Indonesian plaitings products have a comparative advantage in several countries with the highest average RCA value in Denmark at 31.23. Indonesian plaitings products are competitive in the USA, Denmark and Japan, with an EPD category of 'rising star'. In USA and Denmark, the export potential of Indonesian plaitings products is 'optimistic', while in Netherland, Germany, and Spain it is 'less potential'.